Law & ethics for medical careers - Judson, Karen
This text prepares students to understand the legal and ethical issues inherent to working in a medical office. The text includes informative legal cases, anecdotes, and sidebars related to health-related careers. The 1997 AAMA Role Delineation Areas of Competence was used as a guide for preparing each chapter